Mark Jefferson, Geographer, - Martin, Geoffrey J. (Eastern Michigan University Press, 1968)
Keywords: Jefferson; Mark; 1863-1949; dept.egm; faculty_collection

The Mark Jefferson Paris Peace Conference Diary - Jefferson, Mark; Martin, Geoffrey J. (University Microfilms, 1966)
Keywords: Paris Peace Conference (1919-1920)–Personal narratives; World War; 1914-1918; Peace; dept.egm; faculty_collection

Man and the Earth. - Hoyt, Joseph Bixby (Prentice-Hall, 1962)
Keywords: Human geography; dept.egm; faculty_collection

Africa in Maps. - Martin, Geoffrey J. (W. C. Brown Co, 1962)
Keywords: Africa; Maps; dept.egm; faculty_collection

The evolution of beersheba as an urban center1 - Berman, Mildred (Annals of The Association of American Geographers, 1965)
Beersheba has changed from a small agricultural settlement in pre-Biblical times to a city of importance in modern Israel. The wells and fertile loess soils of the Beersheba Basin have been utilized by all who have occupied the area. From 3300 B.C. to the present, Beersheba has functioned as an oasis, market town, military center, transportation node, and as a traditional gathering place for the Bedouin tribes of the Negev, Israel's southern desert. In 1900, the Ottoman Turks initiated the modern development of Beersheba. After World War I, the British administered the area as part of the Palestine Mandate. With the creation of the state of Israel in 1948, the city began to grow rapidly. In the early 1960′s, Beersheba had a population of over 52,000. It functions as the capital of a region containing over two-thirds of the national area. © 1965, Taylor & Francis Group. All rights reserved.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/068-321-173-909-533 tex.type: [object Object]
Keywords: dept.egm

Israel's dynamic frontier region-the negev - Berman, Mildred (Journal of Geography, 1964)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/017-054-151-255-395 tex.type: [object Object]
Keywords: dept.egm